2005
DOI: 10.1111/j.1365-2435.2005.01033.x
|View full text |Cite
|
Sign up to set email alerts
|

Do faster starts increase the probability of evading predators?

Abstract: Summary1. Nearly all fish evade predation strikes by rapidly accelerating out of the strike path, a behaviour called the fast-start evasion response. The many studies investigating morphological, behavioural and ecological correlates of fast-start performance assume that faster starts increase the probability of evasion. 2. We tested this faster-start hypothesis by measuring the effect of acceleration ability on evasion outcome (success, failure) in Guppies ( Poecilia reticulata ) evading the strike of a natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
465
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 383 publications
(482 citation statements)
references
References 42 publications
14
465
2
1
Order By: Relevance
“…In contrast to the effects of increased UV-B, exposure to PCC caused tadpoles to have increased locomotor performance (figure 2a) and longer survival times in a predator environment (figure 2b). This suggests that an increase in locomotor performance does confer some benefit to survival in a predator environment as one would expect [27], but with regard to the effects of UV-B, there are clearly additional factors that need to be considered when investigating predator-prey interactions. Consideration of behavioural defence mechanisms and the energetic costs associated with exposure to UV-B may provide an explanation for the observed reduction in survival time of tadpoles exposed to the high UV-B treatment.…”
Section: Discussion (A) Independent Effects Of Uv-bmentioning
confidence: 99%
“…In contrast to the effects of increased UV-B, exposure to PCC caused tadpoles to have increased locomotor performance (figure 2a) and longer survival times in a predator environment (figure 2b). This suggests that an increase in locomotor performance does confer some benefit to survival in a predator environment as one would expect [27], but with regard to the effects of UV-B, there are clearly additional factors that need to be considered when investigating predator-prey interactions. Consideration of behavioural defence mechanisms and the energetic costs associated with exposure to UV-B may provide an explanation for the observed reduction in survival time of tadpoles exposed to the high UV-B treatment.…”
Section: Discussion (A) Independent Effects Of Uv-bmentioning
confidence: 99%
“…The most common way of avoiding predation, however, is the escape response, a burst swimming movement shown by most fishes when attacked by a predator (Domenici & Blake 1997). Various characteristics of this response were shown to be fundamental for avoiding predation, such as reaction distance, escape path, distance-derived variables (such as velocity and acceleration) and turning rates ( Walker et al 2005). Previous work has shown that certain morphological defences, such as changes in body shape, can be induced by the presence of predators (Brönmark & Miner 1992).…”
Section: Introductionmentioning
confidence: 99%
“…However, given the trade-offs existing between different body shapes and various swimming functions (Webb 1984a), an induced morphological change may not necessarily imply a cost for all locomotor activities. A large body depth may enhance the acceleration performance during escape locomotion, which is considered crucial for avoiding predation in most fish species (Weihs 1973;Webb 1984a;Domenici & Blake 1997;Godin 1997;Walker et al 2005). Based on the idea of a trade-off between a deep and a shallow body as linked to accelerator versus cruiser characteristics (Webb 1984a), we used two morphs of crucian carp to test the prediction that predatorinduced deep-bodied fishes have higher locomotor performance in escape manoeuvres than shallow-bodied fishes.…”
Section: Introductionmentioning
confidence: 99%
“…While applicable to a wide range of animal systems, we focus on fishes because of their extensive ecological, phylogenetic and phenotypic diversity, as well as their prevalence as model systems for studying speciation, many-to-one mapping, and biomechanics. Predator-prey interactions in fishes have been a major focus of research over the past several decades [28,29], where survival depends on both the ability to escape from predators and to catch prey [30]. Locomotor and feeding traits underlie predator-prey interactions, and both respond to selection and contribute to RI [31,32], making predator-prey interactions central to the study of speciation.…”
Section: Introductionmentioning
confidence: 99%